Operational data integration technique for intelligent profile graduate entrepreneur system - Abu Bakar, Muhamad Shahbani; Ta'a, Azman; Shiratuddin, Norshuhada; Anuar, M. S.; Aljunid, Syed A (INSInet Publications, 2014)
Business Intelligence (BI), which is the process of collecting, analyzing, and transforming data using Data Warehouse (DW) is seen as one of the growing approaches to provide meaningful information for the Malaysian Ministry of Higher Education (MOHE). MOHE is responsible for managing various activities to encourage graduate entrepreneurs to venture into the businesses and ensure that the country has many successful entrepreneurs.Therefore, systematic and accurate information needs to be available for planning, implementing, and monitoring entrepreneurs' performances.This paper proposes the modeling and designing of the graduate entrepreneur profile system-Intelligent Profile Analysis Graduate Entrepreneur (iPAGE) using the BI and data integration approach.Two main methodologies were used namely: Conceptual Design Model Operational Data Store (CoDMODS) and Rapid Application Development (RAD) to model and design this system.The iPAGE was validated and evaluated by users, entrepreneur’s personnel and DW experts.Indeed, the approach will be used to benchmark the development of an entrepreneurial information system in the future.